Myth : a new symposium - Schrempp, Gregory Allen, 1950-; Hansen, William F., 1941- (Indiana University Press, 2002)
Myth: A New Symposium offers a broad-based assessment of the present state of myth study. It is inspired by a revisiting of the influential mid-century work Myth: A Symposium (edited by Thomas Sebeok). A systematic introduction and 15 contributions from a wide spectrum of disciplines offer a range of views on past myth study and suggest directions for the future. Contributors blend theoretical analysis with richly documented historical, ethnographic, and literary illustrations and examples drawn from Native American, classical, medieval, and modern sources.